Kebijakan Dividen dalam Memediasi Profitabilitas dan Leverage terhadap Nilai Perusahaan Manufaktur di Bursa Efek Indonesia - Ida Ayu Ratih Manuari; I Gede Cahyadi Putra; Ni Luh Yonny Kaswari (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2022)
The main goal of companies that have gone public is to maximize the value of the company. Firm value is an investor's view of the level of success of the company's management in managing the resources that have been entrusted to him in one period after going through several process activities over the years which are closely related to stock prices. The purpose of this study is to determine the role of dividend policy in mediating the effect of profitability and leverage on firm value in manufacturing companies listed on the Indonesia Stock Exchange for the period 2018-2020.The sample in this study used manufacturing companies listed on the Indonesia Stock Exchange, totaling 48 companies for 3 years of observation so that the total observations were 144. The sampling used purposive sampling technique. The data analysis technique used is Partial Least Square with the help of SmartPLS 3.0 as a calculation tool.The results showed that profitability and leverage had no effect on firm value. Profitability has a positive effect on dividend policy. Dividend policy has a positive effect on firm value. Leverage has no effect on dividend policy. Policy is able to mediate the relationship between profitability and firm value, while dividend policy is not able to mediate the relationship between leverage and firm value.